Impact of Curie Temperature Variation on Bit Error Rate in Heat-Assisted Magnetic Recording - Kobayashi, T; Nakatani, Y; Fujiwara, Y (Journal of the Magnetics Society of Japan, 2019)
The Curie temperature Tc variation problem in heat-assisted magnetic recording is discussed. We describe the physical implication of the Tc variation problem, and provide ways of improving the writing property by employing our simplified model calculation. The bit error rates for mean Curie temperatures of 600 and 700 K are examined. The Tc variation increases both write-error (WE) and erasure-after-write (EAW). The main related calculation parameters are the grain column number in one bit and the thermal gradient for the down-track direction. Increasing the grain column number is effective in reducing WE and EAW caused by the Tc variation. Furthermore, increasing the thermal gradient is necessary since EAW is high. Although a higher writing field of 12 to 14 kOe is necessary, a bit error rate less than 10-3 can be achieved for recording densities of 4 or 2 Tbpsi under the conditions used in this study even though the standard deviation of the Curie temperature is 4 %.